Patient motivation and adherence to post-surgery rehabilitation exercise recommendations: The influence of physiotherapists’ autonomy supportive behaviors - Chan, Derwin; Lonsdale, C.; Ho, P.; Yung, P.; Chan, K. (W.B. Saunders Co., 2009)
Objective: To investigate the impact of physiotherapists' autonomy-supportive behaviors on patients' motivation and rehabilitation adherence after anterior cruciate ligament (ACL) reconstruction surgery. Design: Retrospective study. Setting: Outpatient orthopedic clinic of a university medical center. Participants: Postsurgery ACL reconstruction patients (N=115; minimum postsurgery interval, 6mo; mean ± SD postsurgery interval, 1.77±0.8y). Interventions: Not applicable. Main Outcome Measures: Questionnaires measuring autonomy support from physiotherapists (Health Care Climate Questionnaire), treatment motivation (Treatment Self-Regulation Questionnaire), and rehabilitation adherence (adapted from the Sport Injury Rehabilitation Adherence Scale and the Patient Self-Report Scales of Their Home-Based Rehabilitation Adherence). Results: Structural equation modeling analyses revealed that patients' treatment motivation mediated the relationship between physiotherapists' autonomy-supportive behaviors and rehabilitation adherence. Autonomy-supportive behavior positively predicted autonomous treatment motivation (β=.22, P<.05). Rehabilitation adherence (R2=.28) was predicted positively by autonomous motivation (β=.64, P<.05) and negatively predicted by controlled motivation (β=−.28, P<.05). Conclusions: These preliminary findings are promising and provide an empirical basis for further research to test the efficacy of autonomy support training designed to increase patients' rehabilitation adherence.